HIV‐MSS: A user‐friendly management support system for better planning of HIV care services. (28th June 2021) - Demir, Eren; Adeyemi, Shola; Kengne, Andre Pascal; Kayode, Gbenga A.; Adeoti, Adekunle
Abstract: The advent of antiretroviral therapy (ART) has transformed HIV infection from a deadly disease to a manageable chronic condition. The life expectancy of people living with HIV has been prolonged dramatically. Therefore, health systems are now confronted with new challenges, with ever‐increasing number of newly diagnosed cases, fuelling the pool of existing patients, with many comorbidities and requiring hospital admissions. Are health systems prepared to handle large and increasing numbers of people with HIV? We developed a HIV‐Management Support System (MSS) to support service evaluation and management using simulation by capturing individual patient's pathways within HIV services in the United Kingdom. Two scenarios were tested: (1) the impact of increasing the number of diagnosed cases in steps of 5% on human resources and (2) the impact of treating all patients with ART on hospital admissions. A 5% increase in newly diagnosed HIV cases increases human resource requirements between 4% and 8%, whereas the impact of treating all HIV patients with ART on hospital admissions is far greater. HIV services are under intense pressure and managing patient and service needs are far more important than ever, hence the development of our HIV MSS is timely, to support better planning of services. Note that the HIV simulation model presented in this study is the first of its kind.